The process of CCC approval / Wan Muhammad Syahmi Thaqif Wan Muhamad Subri - Wan Muhamad Subri, Wan Muhammad Syahmi Thaqif (Universiti Teknologi MARA UiTM,Perak, 2021)
The process for obtaining a Certificate of Completion and Compliance (CCC) begins with the PSP, also known as the Principal Submitting Person, submitting the building plan application through OSC Online. Building inspections and site sanitation inspections are held, during which the construction of the building, as well as construction waste, are inspected to ensure that the building complies with the law and that there is no pollution in the surrounding area. Therefore, a valid CCC certificate and a copy of the CCC are submitted to the developer or owner, and a valid G form is submitted to the local authority's development department. The contractor is responsible for ensuring that the house is constructed in accordance with the plan and area specified in the book Uniforms Building by Law (UBBL 1984). CCC (Certificate Completion and Compliance) is an important part of any construction project because it simplifies everything now and in the future.